(untitled) (Journal of Misan Researches, 2024)
In his book, Muhammad bin Tahir Al-Samawi mixed the schools of grammarians, so his problems were a mixture of Kufic grammar, Basri grammar, and those who followed them from the Baghdadi, Andalusians, and Egyptians who were the owners of grammar schools. He often relied on the appropriateness between chapters in his presentation of grammatical issues, despite the fact that the percentage of opinions to their authors is one of the important matters required by scientific research, but most of the general information in Al-Samawi’s book came without any reference to the doctrine or attributing opinions to their authors. Perhaps his approach in presenting opinions is due to his unwillingness to delve into controversy as many grammarians did, or perhaps he For him, the disagreement is of no benefit or benefit, and sometimes we find him content with presenting the issue, and choosing for himself a doctrine different from what is stated in the main books - and this is what we will explain in its place - or he states an opinion that agrees with one of the doctrines, but he does not stipulate in it what they went for, that is, he is satisfied with the generality of the restriction. Not about him, and sometimes you find him preferring two doctrines at the same time without preferring or choosing one of them. The above gives Al-Samawi a distinctive style in presenting grammatical issues, and at the same time his approach is not devoid of some drawbacks, such as digression in some controversial issues, as well as ambiguity and brevity in presenting the issues, and more than that, he is criticized for leaving many grammatical issues - especially controversial ones - blank. It is evidence that may help the reader understand the issue, and this is what we clearly see in many of the chapters of its three sections.